Donor–Acceptor Type Dopant‐Free, Polymeric Hole Transport Material for Planar Perovskite Solar Cells (19.8%). Issue 4 (22nd September 2017) - Kim, Guan‐Woo; Lee, Junwoo; Kang, Gyeongho; Kim, Taewan; Park, Taiho
Abstract: Organic–inorganic hybrid perovskite has led to the development of new solar cells with outstanding efficiency. In perovskite solar cells (PSCs), perovskite is sandwiched between a working electrode (fluorine‐doped tin oxide) and a counter electrode (gold, Au). In order to transport charges and block opposite charges, charge transport layers are inserted between perovskite and the electrodes. In particular, a hole transport layer is important because it generally prevents perovskite from exposure to air. Therefore, it is necessary to investigate dopant‐free and hydrophobic polymeric hole transport materials (HTMs). In this study, a novel polymeric HTM (PTEG) is synthesized by controlling the solubility using a tetraethylene glycol group. The planar‐PSC employing PTEG exhibits an efficiency of 19.8% without any dopants, which corresponds to the highest value reported to date. This study offers a fundamental strategy for designing and synthesizing various polymeric HTMs. Abstract : This study examines a highly efficient perovskite solar cell (PSC) that employs a dopant‐free hole transport material (HTM) . A polymeric HTM (PTEG) combined with a tetraethylene glycol group is synthesized and systematically characterized. Results indicate that the PSC employing PTEG exhibits the highest efficiency (19.8%) in the planar device.